Investigation of Preschool Education Teachers, Preschool Children and Mothers' Opinions on Artificial Intelligence - BALABAN DAĞAL, ASUDE (My University, 2024)
Nowadays, artificial intelligence, which is used in different fields with the increase in the number of works and transactions carried out in digital environment, is also used in the field of education. The main purpose of this study is to examine the views about artificial intelligence of preschool children, their mothers and teachers. The research was planned with phenomenology research design, one of the qualitative research methods. The study group of the research was formed by selecting a total of 30 people in the convenience sampling method, including 5 preschool teachers teaching in public and private independent kindergartens, 1 student from each teacher's 5-year-old class and his/her mother. The data were collected through interviews and the interview questions were prepared by the researchers as open-ended questions. According to the results of the research, it was concluded that although the teachers defined artificial intelligence on the correct scientific basis, they did not have sufficient knowledge, did not use it in educational environments to increase the productivity of children and were worried. Considering the answers given by mothers and children to the questions about artificial intelligence, it can be interpreted that artificial intelligence is not defined correctly and there is a lack of knowledge, mothers have concerns that artificial intelligence may be harmful for their children, and children see artificial intelligence as a living being that they can talk to. Keywords: Artificial intelligence, Preschool teacher, Early childhood
Keywords: Artificial intelligence; Preschool teacher; Early childhood